MANAJEMEN MUTU BERBASIS SEKOLAH: KONSEP DAN IMPLEMENTASINYA DALAM PENINGKATAN MUTU PENDIDIKAN - Rosmiati ramli; Muthmainnah Al-Uswan Sumule; Darnita; Syahwal (STKIP Subang, 2026)
School-Based Quality Management is one of the education management approaches that gives authority to schools to manage resources independently to improve the quality of education. This research aims to analyze the concept of School-Based Quality Management and examine its implementation in an effort to improve the quality of education. The research uses a qualitative approach with the type of library research. Data was obtained through documentation studies of various literature sources in the form of books, journal articles, research results, and relevant scientific documents. Data analysis is carried out using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that School-Based Quality Management is an education management model based on the principles of independence, participation, transparency, accountability, and sustainability. The implementation of School-Based Quality Management is carried out through the process of planning, implementing, supervising, and evaluating educational programs by involving all school residents and the community. The successful implementation of School-Based Quality Management is influenced by the leadership of the principal, the professionalism of teachers, community participation, and effective and accountable school management. Although still facing various obstacles, such as limited human resources and infrastructure, School-Based Quality Management has proven to make a positive contribution to improving the quality of education. Therefore, School-Based Quality Management can be an effective strategy in realizing quality, competitive, and sustainable education.